Kenapa Kurikulum Selalu Berubah? - Anisa Reflanda Putri; Fheni Nur Ahlami; Shara Suci Novipaloka (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
The curriculum is an important component of education in Indonesia because it is a set of plans and regulations regarding the objectives, content, teaching materials, and methods used in learning that will cause the quality of education in a country to rise or fall through its community resources. Why does the curriculum always change? Because there is a need to adapt to the times, technology, and community demands. The establishment of the curriculum began in 1947 with the first curriculum in Indonesia, the 1947 Lesson Plan Curriculum, up to the Merdeka Curriculum. Although curriculum changes aim to improve the quality of education, their implementation often faces several obstacles. The research method used by the researcher is a qualitative study through literature review of educational documents, books, and scientific articles related to the topic, enabling the researcher to obtain relevant and up-to-date information about the curriculum in Indonesia. This study aims to examine the development and changes in the national education curriculum in Indonesia from 1947 to the current Merdeka Curriculum.